2015
DOI: 10.3390/ijms17010002
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Neuroendocrine Disturbances over Time: Longitudinal Findings in Patients after Traumatic Brain Injury and Subarachnoid Hemorrhage

Abstract: Previous reports suggest that neuroendocrine disturbances in patients with traumatic brain injury (TBI) or aneurysmal subarachnoid hemorrhage (SAH) may still develop or resolve months or even years after the trauma. We investigated a cohort of n = 168 patients (81 patients after TBI and 87 patients after SAH) in whom hormone levels had been determined at various time points to assess the course and pattern of hormonal insufficiencies. Data were analyzed using three different criteria: (1) patients with lowered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Lastly, uncertainty exists as to whether development of pituitary dysfunction after SAH is permanent. Several authors including a recent meta-analysis, have demonstrated that the prevalence of pituitary dysfunction including that of the somatotrophic axis, can change with time [ 14 , 19 , 22 , 23 , 29 , 39 , 47 , 50 ]. As such it remains unclear whether pituitary function should be continually re-assessed in SAH patients, and if so, at what time points.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, uncertainty exists as to whether development of pituitary dysfunction after SAH is permanent. Several authors including a recent meta-analysis, have demonstrated that the prevalence of pituitary dysfunction including that of the somatotrophic axis, can change with time [ 14 , 19 , 22 , 23 , 29 , 39 , 47 , 50 ]. As such it remains unclear whether pituitary function should be continually re-assessed in SAH patients, and if so, at what time points.…”
Section: Discussionmentioning
confidence: 99%
“…The literature contains reported rates of chronic hypopituitarism post-TBI which range from 15% to 69% (3,19,32,33,43,46,47,48,49,50,51,52,53,54,55,56,57,58,59). Published cohort studies vary widely in methods of patient selection, severity of head injury included and the timing and methods of testing for hypopituitarism ( Table 1).…”
Section: Anterior Pituitarymentioning
confidence: 99%
“…Previously we have shown that neuroendocrine disturbances often persist over years after TBI or SAH (5) with the highest prevalence being observed 1–2 years post-injury. However, transient deficiency is also a known phenomenon, and patients may potentially recover from gonadotropic and somatotropic insufficiency (6).…”
Section: Introductionmentioning
confidence: 99%